SISTEM INFORMASI PENERIMAAN PAJAK DAN RETRIBUSI BERBASIS CLIENT-SERVER PADA DINAS PENDAPATAN DAERAH PROPINSI LAMPUNG - Rima Maulina (IIB Darmajaya, 2011)
The process of tax revenue, and the Department of Revenue Lampung province is managed by two sub-sections namely kasi kasi taxes and levies. In managing data and tax revenue, there are problems that the admission process is only recorded in the receipt book so that the administrative difficulties in merekap report every day / month which allow for human error (human error) in the process perekapannya. To improve performance in data processing taxes and levies are necessary computer tools with software designed specifically for the sake of it. With this system the problems related to data processing tax revenues and levies can be resolved. These programs facilitate the search and the lawyer's input data related to the data receipts taxes and levies, as well as facilitate in making the report, so that the information provided relating to such data can be better. With the creation of data processing applications taxes and levies on the Department of Revenue issues related to taxes and levies can be solved by good and does not affect the reporting. Keywords: Taxes and Levies